2005
DOI: 10.1177/014107680509800306
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Automated Blood Pressure Devices used by Hypertensive Patients

Abstract: SUMMARYAutomated blood pressure (BP) devices are used by many hypertensive patients in Hong Kong, with or without medical advice. At two community clinics, we invited hypertensive patients aged between 40 and 70 years who used such a device to fill in a questionnaire and to have four sets of BP measurements, automated and mercury, at two visits. Of 290 hypertensive patients 120 fulfilled the criteria, and 73 of these agreed to participate. 53 devices measured arm BP, 21 measured forearm BP. The agreement betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Similar to our findings, previous studies have also showed a significant proportion of inaccurate home BP devices [ 16 18 , 22 28 ]. However, differences in methodologies used in these past studies including the generation of HBP monitors assessed, threshold used to determine inaccuracy, type and number of observers who assessed the accuracy limit the comparison of our results to those reported by these studies.…”
Section: Discussionsupporting
confidence: 93%
“…Similar to our findings, previous studies have also showed a significant proportion of inaccurate home BP devices [ 16 18 , 22 28 ]. However, differences in methodologies used in these past studies including the generation of HBP monitors assessed, threshold used to determine inaccuracy, type and number of observers who assessed the accuracy limit the comparison of our results to those reported by these studies.…”
Section: Discussionsupporting
confidence: 93%
“…BP measurement is a relatively simple procedure, but several factors such as observer, environment, patient, and equipment can impact BP measurement results. Equipment-related errors in the measurement of BP are not uncommon [13,[15][16][17][18][19][20]. We recently investigated the accuracy of home sphygmomanometers and reviewed earlier studies evaluating the frequency of device-related errors [13].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies had been conducted in hospital or primary care settings, [15][16][17] and only a few studies [18][19][20] evaluated the accuracy of home sphygmomanometers.…”
Section: Discussionmentioning
confidence: 99%
“…Obese individuals may not fit available cuff sizes, and patients with anxiety syndromes may overuse these devices and suffer panic attacks with secondary blood pressure elevations. Studies have shown that 40% of patients do not read the instructions, 50% of patients lack any training in measuring blood pressure, and patients frequently fabricate low numbers and omit elevated numbers 10,11 . These are obstacles that can be overcome by careful selection of patients, training with regard to blood pressure technique, and the use of home devices containing memory chips.…”
Section: Discussionmentioning
confidence: 99%